Challenging the putative structure of mannan in wheat (Triticum aestivum) endosperm. (15th November 2019) - Verhertbruggen, Yves; Falourd, Xavier; Sterner, Marlayna; Guillon, Fabienne; Girousse, Christine; Foucat, Loïc; Le Gall, Sophie; Chateigner-Boutin, Anne-Laure; Saulnier, Luc
Highlights: Mannan-enriched extracts were obtained from wheat endosperm and characterized. In wheat endosperm, mannan is made of short unsubstituted chains of mannose. Despite its linear structure, wheat mannan is (partly) water soluble. No interaction between wheat mannan and other cell wall components were detected. Abstract: In wheat endosperm, mannan, is poorly documented. Nevertheless, this hemicellulosic polysaccharide might have a determinant role in wheat grain development since, in Arabidopsis thaliana, mutants with a reduced amount of mannan show an altered seed development. In order to gain knowledge about mannan in wheat, we have determined its biochemical structure in wheat endosperm where mannose content is about 0.2% (dry weight basis). We developed a method of enzymatic fingerprinting and isolated mannan-enriched fractions to decipher its fine structure. Although it is widely accepted that the class of mannan present in grass cell walls is glucomannan, our data indicate that, in wheat endosperm, this hemicellulose is only represented by short unsubstituted chains of 1, 4 linked D-mannose residues and is slightly acetylated. Our study provides information regarding the interactions of mannan with other cell wall components and help to progress towards the understanding of monocot cell wall architecture and the mannan synthesis in wheat endosperm.